THE EFFECT OF AUDIT FEE, AUDIT TENURE, AND COMPANY SIZE ON AUDIT QUALITY : (An Empirical Study Of Manufacturing Companies In The Food & Beverage Sub-Sector Listed on The Indonesia Stock Exchange 2019-2023) - Nadila Ayuni; Emi Masyitah; Ina Liswanty (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the influence of audit fees, audit Tenure, and company size on audit quality in manufacturing companies in the Food & beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The underlying phenomenon of this research is the rise in cases of financial statement manipulation, which have raised public doubts about audit quality. The research method used is a quantitative associative approach, utilizing secondary data in the form of companies' annual financial reports. The research sample was obtained using a purposive sampling technique of 17 companies. Data analysis was performed using logistic regression. The analysis results indicate that audit fees, audit Tenure, and company size have no significant effect. Simultaneously, all three independent variables influence audit quality. The Nagelkerke R Square value of 0.057 indicates that the independent variables are able to explain the variation in audit quality by a percentage, while the remainder is influenced by other factors outside the model. This finding confirms that the amount of audit fees, length of audit engagement, and company size are not always determining factors.